Pengaruh Penggunaan Media Pembelajaran Berbasis ICT (Information Communication and Technology) Terhadap Perkembangan Bahasa Inggris Awal Anak Usia 5-6 Tahun - Yesi Novitasari; Sri Wahyuni; Lastri Situmorang (Universitas Lancang Kuning, 2021)
This research have a purpose to determine the influence of ICT (Information Communication and Technology) -based learning media on the development of early English children aged 5-6 years. The research method used is true experimental research. The subject of this research is a child aged 5-6 years in grade B1 and B2 TK Daniel HKBP Rumbai, the number of groups B1 TK Daniel HKBP Rumbai is 15 children consisting of 6 boys, 9 girls and the number of groups B2 TK Daniel HKBP Rumbai is 15 children consist of 7 boys and 8 girls. Data collection tools used in the form of an early English developmental observation sheet of children aged 5-6 years after obtaining ICT-based learning media treatment. From the results of the t-test showed that the value of asymp. Significant (2-tailed) by 0.013 to a significant value of < 0.05. Hypothesis is accepted means that ICT-based learning media able to make English skills early children aged 5-6 years in TK Daniel HKBP Rumbai better. Therefore, researchers provide advice so that educators can make ICT-based learning media as an alternative in learning activities especially on early childhood English recognition